Public policies for the social and solidarity economy in Colombia in times of pandemic and crisis of neoliberalism - Martínez Collazos, Jarrison (Cooperativismo & Desarrollo, 2023)
The civilizing crisis manifested in the biological, environmental, economic, social, and political events that are taking place has increased the search for alternatives that contribute to creating a society that is respectful of the environment, that overcomes the deep social inequality and places ethical and humanists. This article analyzes the structural crisis that the so-called neoliberal model is experiencing, analyzes the alternatives that have been proposed from the social and solidarity economy, such as the public policies drawn up by the Colombian State for the development of said economy, suggesting changes in the new context that is occurring in Colombian society.